Ethical framework for designing autonomous intelligent systems - Jaana Leikas; Raija A. Koivisto; Nadezhda Gotcheva (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
To gain the potential benefit of autonomous intelligent systems, their design and development need to be aligned with fundamental values and ethical principles. We need new design approaches, methodologies and processes to deploy ethical thought and action in the contexts of autonomous intelligent systems. To open this discussion, this article presents a review of ethical principles in the context of artificial intelligence design, and introduces an ethical framework for designing autonomous intelligent systems. The framework is based on an iterative, multidisciplinary perspective yet a systematic discussion during an Autonomous Intelligent Systems (AIS) design process, and on relevant ethical principles for the concept design of autonomous systems. We propose using scenarios as a tool to capture the essential user's or stakeholder's specific qualitative information, which is needed for a systematic analysis of ethical issues in the specific design case.
Keywords: 650; autonomous systems; autonomous intelligent systems; artificial intelligence; AI; ethics; design